Revenge and reconciliation - Gandhi, Rajmohan (New Delhi ; New York, NY : Penguin Books, 1999)
History of India from the earliest times till present, with an emphasis on ethnic conflicts.
Includes bibliographical references (p. 439-446) and index.
Keywords: India -- History; India -- Ethnic relations